Ambiguous value of Haemophilus influenzae isolation in Guillain-Barré and Fisher syndromes. Issue 12 (16th November 2005) - Koga, M; Koike, S; Hirata, K; Yuki, N
Abstract : Background: Haemophilus influenzae is considered a causative agent of Guillain-Barré syndrome (GBS) and Fisher syndrome, but the frequency of this infection in GBS is controversial. Objective: To determine whether isolation of H influenzae indicates it is a causative agent in GBS and Fisher syndrome. Results: Four (15%) of 27 patients with GBS and Fisher syndrome in whom H influenzae was isolated were also seropositive for Campylobacter jejuni . Antiganglioside IgG antibodies in these four patients did not cross react with their H influenzae lipo-oligosaccharides, whereas antiganglioside antibodies in the four patients with positive serology for H influenzae did. Conclusions: The findings suggest that H influenzae isolation is not always indicative of the causative agent in these syndromes and that tests for other infections should be made, even in cases of positive culture.